Sectoral Technology and Structural Transformation - Berthold Herrendorf; Christopher Herrington; Ákos Valentinyi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
This paper assesses the importance for structural transformation of three features of sectoral technology: labor-augmenting technological progress, capital intensity, and substitutability between capital and labor. We estimate CES production functions for agriculture, manufacturing, and services on postwar US data and compare them with Cobb-Douglas production functions with different and with equal capital shares. We find that sectoral differences in labor-augmenting technological progress are the main force behind the trends in observed relative prices and sectoral labor. As a result, sectoral Cobb-Douglas production functions with equal capital shares (which by construction abstract from differences in the elasticity of substitution and in capital shares) do a good job of capturing the postwar US structural transformation.
Keywords: O11; O14; 330; CES production function; Cobb-Douglas production function; structural transformation; elasticity of substitution; Strukturwandel; Faktorsubstitution; CES-Produktionsfunktion; Cobb-Douglas-Produktionsfunktion; Technischer Fortschritt; Mehrsektoren-Modell; Theorie; Schätzung; USA